2021
DOI: 10.21608/asnj.2021.56497.1096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tele-nursing Instructions on Women Knowledge and Beliefs about Cervical Cancer Prevention

Abstract: Worldwide, the cervical cancer considered the most frequent gynecological cancer among women. Effective primary and secondary prevention approaches will prevent most cervical cancer cases. Aim of the study: is to assess the level of women's knowledge and beliefs regarding cervical cancer prevention and to implement and examine the effectiveness of tele-nursing instructions on women based on Health Belief Model. Methods: A quasi-experimental design was used. This study was conducted at primary health care cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Results of the current study revealed that, most of the studied women had unsatisfactory level of total knowledge score in the pretest. This finding is supported by many recent Egyptian studies (Aziz et al, 2022;Ahmed, 2022;Amin et al, 2021;Mohamed et al, 2021). The limited knowledge about cervical cancer prior to the intervention in this study can partly be attributed to the lack of a national strategy for executing outreach and educational initiatives aimed at the general populace, particularly women of reproductive age.…”
Section: Discussionsupporting
confidence: 67%
“…Results of the current study revealed that, most of the studied women had unsatisfactory level of total knowledge score in the pretest. This finding is supported by many recent Egyptian studies (Aziz et al, 2022;Ahmed, 2022;Amin et al, 2021;Mohamed et al, 2021). The limited knowledge about cervical cancer prior to the intervention in this study can partly be attributed to the lack of a national strategy for executing outreach and educational initiatives aimed at the general populace, particularly women of reproductive age.…”
Section: Discussionsupporting
confidence: 67%
“…Recent research conducted in Saudi Arabia on women’s understanding of cervical cancer consistently highlights the need for educational interventions to improve knowledge. One such intervention, described in El-Sayed et al’s [ 30 ] study, utilized tele-nursing based on the Health Belief Model to significantly improve women’s beliefs and knowledge about preventing cervical cancer. Tele-nursing utilizes information and telecommunications technology to deliver, manage, and coordinate care and services, providing quick access to specialist knowledge and improving patient care.…”
Section: Discussionmentioning
confidence: 99%